Louisa May Alcott’s Changing Views on Women, Work, and Marriage in Work - Jelena Šesnić (European Journal of American Studies)
Louisa May Alcott’s intriguing and productive mix of fiction and auto-fiction suffuses the experience of the female protagonist of her Transcendentalist Bildungsroman Work (1873). The text, therefore, engages intersecting but distinct discourses of femininity, domesticity, and individual emancipation. The novel proposes a new direction by placing women squarely in the public sphere of labor and social relations, even though that move is qualified by normative and sentimentalist constraints for middle-class characters. Still, Alcott ably marshals reformist and Transcendentalist ideas to prove that the feminine Bildung requires self-growth, education, work and a variety of social and affective relationships.